Growth kinetic and characterization of tetrapod ZnO nanostructures - N. Hongsith (2018)
Tetrapod ZnO nanostructures (T-ZnO) were synthesized by an oxidation reaction technique by heating the mixture of zinc powder and hydrogen peroxide solution at 1000 ring operatorC under normal atmospheric pressure. The cross-sectional size which was determined at the middle of the legs and the length of T-ZnO is about 200-1000 nm and 1-5 μm, respectively. XRD, EDS and TEM results confirmed that T-ZnO is a hexagonal structure and has a growth direction along [0001] direction. A growth model of T-ZnO by anisotropic growth via a vapor-solid mechanism with 3D tetrahedral nucleus as a seed was proposed. The 3D tetrahedral nuclei form by accumulation and then, condensation of ZnO vapor due to a supersaturation condition. These 3D nuclei first grow along the c-axis in four variants of tetrahedral axes due to symmetrical structure before finally forming the four-leg structure of T-ZnO. Evidence to confirm this growth model were the kinked Y-shape, X-shape, and H-shape of the projected images of grain boundaries observed by TEM. This growth model could be generalized to explain other materials having a similar hexagonal structure such as GaN. © 2009 Elsevier Ltd. All rights reserved.